2018
DOI: 10.1007/s00380-018-1140-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in hemodynamic responses and long-term survival to optimal medical therapy in patients with pulmonary arterial hypertension

Abstract: It is widely known that the incidence of pulmonary arterial hypertension (PAH) is higher in female, whereas prognosis is poorer in male patients. However, sex differences in hemodynamic response to and long-term prognosis with PAH-targeted treatment in the modern era remain to be fully elucidated. We examined the long-term prognosis of 129 consecutive PAH patients (34 males and 95 females) diagnosed in our hospital from April 1999 to October 2014, and assessed hemodynamic changes in response to PAH-targeted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 51 publications
(70 reference statements)
2
19
0
Order By: Relevance
“…Although developing more severe disease, male patients show less improvements of hemodynamics and right ventricular functions in response to current therapies, which is linked with worse overall long-term prognosis. 6 Our data, however, show that pharmacological inhibition of ILK with Cpd22 markedly attenuated pulmonary vascular remodeling, PH, and RV hypertrophy in males, which is in good agreement with our previous studies on male mice with SuHx-induced PH. 9 Female rats, treated with Cpd22, showed no significant decrease of pulmonary vascular remodeling, PH, RV hypertrophy, and RV EDP and did not improve RV contractility.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although developing more severe disease, male patients show less improvements of hemodynamics and right ventricular functions in response to current therapies, which is linked with worse overall long-term prognosis. 6 Our data, however, show that pharmacological inhibition of ILK with Cpd22 markedly attenuated pulmonary vascular remodeling, PH, and RV hypertrophy in males, which is in good agreement with our previous studies on male mice with SuHx-induced PH. 9 Female rats, treated with Cpd22, showed no significant decrease of pulmonary vascular remodeling, PH, RV hypertrophy, and RV EDP and did not improve RV contractility.…”
Section: Discussionsupporting
confidence: 93%
“…3 PAH is predominantly female disease. Male patients, however, develop more severe disease and respond poorer to current therapies, [4][5][6] suggesting that responses to novel anti-proliferative therapeutics could also be gender-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of this strategy had increased its use substantially all over Japan by approximately 2010, and several centers in Japan have reported that a reduction of mPAP was found to be related to improved prognosis. 8 , 14 NYHA and echocardiography data, the reported important diagnostic markers, were not included in this paper. The purpose of this study was to determine the treatment target for improving IPAH, and not to identify the factors related to prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In idiopathic PAH at baseline, men have lower RV ejection fraction and stroke volume compared to age-matched females despite similar pulmonary artery pressure (PAP) and PVR [ 26 ]. Two independent investigations demonstrated that after initiation of PAH-specific therapy, only women show improvement in RV function despite similar improvement in PVR between the sexes [ 27 , 28 ]. Disparate RV recovery is thought to explain, at least in part, the poorer prognosis seen in men.…”
Section: The “Estrogen Puzzle” Of Pahmentioning
confidence: 99%